The Colorado and Virgin Rivers before Lake Mead - Joe Weber (Journal of Maps, 2018)
In 1936, the completion of Hoover Dam on the Colorado River in Nevada and Arizona created Lake Mead, the largest reservoir in the United States. When the lake reached capacity in 1941 several canyons and valleys were flooded, along with two towns, several mines, farm fields, and roads. The area had not been surveyed archaeologically and little detailed information exists about the vegetation and geology of this region. The map reconstructions the geography of the area in 1930 before Lake Mead was constructed, showing roads, towns, mines, physical features, and private property, and was created using a range of historical United States Geological Survey (USGS) maps, a digital elevation model (DEM) providing underwater elevations, and other historical sources. The map includes portions of southern Nevada and northwest Arizona, United States, and is at a scale of 1:210,000. It is hoped that the map may draw attention to the lost geographies of other localities across the United States due to the more than 84,000 dams and reservoirs in the country.